Impact of Intolerance of Uncertainty on Depression in College Students During the COVID-19 Pandemic: Coping Strategies as Mediators - Peng Wan PhD; Jinsheng Hu PhD; Chang Su MD; Qi Li PhD (SAGE Publishing, 2024)
The coronavirus disease (COVID-19) pandemic and associated infection control measures have introduced significant uncertainty, and the unbearable nature of this uncertainty has heightened the risk of mental health issues among college students. This study aimed to assess the impact of unbearable uncertainty during the COVID-19 pandemic on college students' depression and investigate the mediating role of coping strategies between unbearable uncertainty and depression. A cross-sectional survey was conducted with 714 Chinese university students using the Intolerance of Uncertainty Scale (IUS-12), Brief Coping Style Questionnaire, and Beck Depression Inventory (BDI-II). SPSS PROCESS was used for the partial correlation analyses and structural equation modeling. (1) Negative coping strategies were significantly positively correlated with intolerable uncertainty and depressive symptoms, while positive coping strategies were negatively correlated with both intolerable uncertainty and depressive symptoms. Intolerable uncertainty was significantly and positively correlated with depressive symptoms. (2) Intolerance to uncertainty significantly predicted depressive symptoms. Both negative and positive coping strategies played parallel mediating roles in the relationship between unbearable uncertainty and depressive symptoms among college students. This study found that coping strategies played a mediating role in the relationship between unbearable uncertainty and depression during the pandemic in 2019. Future research and interventions should focus on enhancing tolerance of uncertainty and promoting positive coping strategies.